A Novel Approach for Phishing Emails Real Time Classification Using K-Means Algorithm - Vidya Mhaske-Dhamdhere; Sandeep Vanjale (Institute of Advanced Engineering and Science, 2018)
The dangers phishing becomes considerably bigger problem in online networking, for example, Facebook, twitter and Google+.. In this paper we are mainly focus on a novel approach of real time phishing email classification using machine learning algorithm. We use random forest, Decision tree with J48 ,naïve Bayes we use spam base dataset. On spam base dataset random forest algorithm work best which give true positive 97.2% and falsie negative is 0.88% and give correctly classification 94.82% and incorrectly classification 5.17%.